Extremely resistant tuberculosis (XDR-TB), history and current situation - Mendoza Ticona, Alberto (2018)
Diseases caused by Mycobacteria are an important area within infectious diseases in mankinds history, and since early times conditions such as tuberculosis (TB) and leprosy (Hansens disease) had already been described. This also holds true for diseases caused by other Mycobacteria.Tuberculosis is a mycobacterial disease caused by Mycobacteria tuberculosis complex, being Mycobacterium tuberculosis one of its most conspicuous components. This microorganism has perfected its mechanisms for survival, allowing it to develop resistance against antituberculous therapy.As it is the case for other microorganisms, the basis for M. tuberculosis resistance is the selection of mutant bacteria with innate resistance to currently available antituberculous drugs; so, by virtue of this adaptive and evolutive phenomenon, there is the emergence of a subpopulation of M. tuberculosis that is extremely resistant to multiple antituberculous drugs, and the survival prognosis for patients with TB disease caused by these particular microorganism is quite poor, so different to that in subpopulations with TB disease caused by multidrug-resistant (MDR-TB) M. tuberculosis.Until June 2008, XDR-TB had been reported in 49 countries, Peru amongst them. The occurrence of a single case of XDR-TB and its contacts must be approached as a sanitary emergency. The development of XDR-TB reflects a weakening of healthcare services, particularly those at the first level or primary care. The two most important risk factors associated with the occurrence of XDR-TB are: 1) failure with a second-line antituberculous drug regimen including one injectable drug and a fluoroquinolone, and 2) close contact with any individual with documented XDR-TB who is failing with a second-line antituberculous drug regimen. XDR-TB must be approached as a sanitary emergency, so adequate financial resources must be allocated for controlling its spread, which means having early diagnosis, timely therapy, integral management and adequate support for the patients and his/her relatives; also, index cases must be isolated until they become non-infectant.